Disaster mitigation-based environmental management model: a study on ten thousand hills, Tasikmalaya City, West Java. Issue 1 (1st February 2022) - Fadjarajani, S; As'ari, R
Abstract: Tasikmalaya seen from the physiographical aspect has its own uniqueness because it has many hills known as the ten thousand hills. The Ten thousand has functions, namely: geological, ecological, hydrological, aesthetic, economic, micro-climatological, natural defense/fortress (buffer zone), as well as education and tourism functions. The method used in this research is descriptive with field observation data collection techniques based on Satellite Imagery analysis.. The method used in this research is descriptive with field observation data collection techniques based on Satellite Imagery analysis. Data analysis is based on satellite imagery data processing with ArcGIS which was developed. The facts on the ground show that the extinction rate of the hill reaches 70%. One of the driving factors for the extinction of the hill was the mining of mineral. The distribution pattern and factual conditions in the field showed that 41.67% of the hills experienced extinction and 58.33% of the hills were heavily damaged by sand mining. This disaster mitigation-based environmental management model includes: 1) Zoning of hill areas based on conservation functions, 2) community participation based on economic improvement. Ten thousand hill zoning and community participation based on economic improvement can be used as role models for environmental management based on disaster mitigation in Tasikmalaya which is located in the ten thousand hill area.